Efektifitas Perizinan Berusaha Berbasis Risiko dalam Rangka Kemudahan Berusaha - Erni Erni; Febri Jaya (Universitas Batanghari Jambi, 2022)
Every businessmen in Indonesia, both individuals and legal entities, is required to have legality in the form of a business license before starting or running a business activity. Based on Law Number 11 of 2020 concerning Job Creation, the current business license is risk-based business license, namely a business license based on the level of business scale and risk determination of business activities. The Online Single Submission Risk Based Approach (OSS-RBA) system is a system that integrated with the OSS institution which functions to administer risk-based business licensing. The implementation of risk-based business licensing through OSS-RBA system is expected to provide speed, certainty, convenience and transparency for businessman. As a result, it creates ease of doing business that can increased investment in Indonesia. This study aims to determine how the implementation and effectiveness of risk-based business licensing in providing ease of doing business from perspective of businessmen. This research used non-doctrinal or empirical legal method. The result of this study is that risk-based business licensing through OSS-RBA system still has obstacles where the system and its application are still in the process of being improved so the effectiveness of the new business licensing arrangements and systems are still not optimal.